Advance care planning for vulnerable older adults within an Accountable Care Organization: study protocol for the IMPACT randomised controlled trial. Issue 12 (15th December 2019) - Gabbard, Jennifer; Pajewski, NM; Callahan, Kathryn E; Dharod, Ajay; Foley, Kristie; Ferris, Keren; Moses, Adam; Grey, Carl; Williamson, Jeff
Abstract : Introduction: Patients with multimorbidity plus additional impairments (eg, mobility limitations, disability, cognitive impairments or frailty) are at the highest risk for poor healthcare outcomes. Advanced care planning (ACP) provides patients and their surrogates the opportunity to discuss their goals, values and priorities for healthcare—particularly in the context of end-of-life care. ACP discussions promote more person-centred care; however, it is currently underused. There is a tremendous need for systematic, scalable approaches to individualised ACP that promotes patient and family engagement. Here we describe the study protocol for a randomised effectiveness trial of a nurse navigator and informatics intervention designed to improve the documentation and quality of ACP discussions. Methods and analysis: This is a randomised, pragmatic, effectiveness trial; patients aged 65 years and older who have multimorbidity plus impairments in either physical function (eg, mobility limitations or disability) or cognition, and/or frailty within an affiliated Accountable Care Organization were eligible. The electronic health record was used to develop an automatic prescreening system for eligible patients (n=765) and participants were randomised in a 1:1 ratio to either the nurse navigator-led ACP pathway or usual care. Our primary outcomes are documentation of ACP discussions within the EHR along with the quality of ACP discussions. Secondary outcomes include a broad range of ACP actions (eg, usage of ACP billing codes, choosing a surrogate decision-maker and advance directive documentation). Outcomes will be measured over 12 months of follow-up. Ethics and dissemination: This study has been approved by the appropriate Institutional Review Boards and is guided by input from patient and clinical advisory boards. The results of this study will inform a scalable solution to ACP discussions throughout our healthcare system and statewide. Trials registration number: NCT03609658 .